Readiness of English Language Lecturers in Implementing Online Learning Based on Their ICT Skills and Needs - Nurdin Noni; Riny Jefri; Lely Novia (Seminar Nasional LP2M UNM, 2021)
Abstract. This study focuses on the lecturers’ readiness in the English departments to apply online learning. The research objectives are to explore (1) the level of lecturers’ readiness of in the English departments to apply online learning based on their knowledge and skills; and (2) the lecturers’ needs in relation to their readiness in implementing online learning. This research uses descriptive quantitative method. The number of respondents who filled out the questionnaire was 121 consisting of 58 lecturers from state universities and 63 from private universities. They are spread over 48 public and private universities in Indonesia. The instrument used is a questionnaire with a Likert scale. The data collected through questionnaires were analyzed using descriptive analysis techniques. The results of this study indicate that (1) the level of lecturers’ readiness is in the high category based on their level of knowledge and ICT skills; and (2) there are 3 main aspects needed, namely the need for ICT facilities, institutional support, and ICT training in learning.Keywords: readiness, online learning, ICT skills